Protective effects of Aristolochia longa and Aquilaria malaccensis against lead induced acute liver injury in rats - Samir, Derouiche; Khaoula, Zeghib; Safa, Gharbi; Yahia, Khelef; Anouar, Feriani (Journal of acute disease, 2017)
Objective: To investigate the protective effects of Aristolochia longa (A. longa) and Aquilaria malaccensis (A. malaccensis) on acute hepatotoxicity induced by lead in female albino rats. Methods: Twenty five (25) apparently healthy female Wistar rats were randomly divided into five groups of five rats in each: control, Pb, Pb + A. longa (Ar), Pb+ A. malaccensis (Aq), and Pb+ A. longa (Ar) + A. malaccensis (Aq) lead (100 mg/kg b.w.) as Pb (C2H3O2)2 added in their drinking water for 75 days. A. longa (rhizome powder at a dose of 10 g/kg of diet ) and A. malaccensis (heartwood powder at a dose 10 g/kg of diet) were added to the feed during the last 15 days of lead exposed in the animals. Results: Obtained results revealed that lead treatment caused a significant increase in serum GOT, GPT and ALP activities and in liver of MDA level and CAT activity. In contrast, it led to an decrease in the liver GOT, GPT and GST activities and in GSH level in rats. Also, the results clearly showed that lead causes alterations of hepatic tissue in comparison with controls. Our results showed that treatment with A. malaccensis and A. longa a partial correction of the previous parameters. The histological observations confirmed the hepatoprotection results by the biochemical parameters. Conclusions: Results demonstrated beneficial effects of A. longa and A. malaccensis treatment in Pb-induced oxidative stress and tissue damage in liver.